PENGARUH AKTIVITAS KEPROFESIAN, KEPEMIMPINAN KEPALA SEKOLAH DAN KEIKUTSERTAAN DALAM DIKLAT TERHADAP KINERJA GURU SMP DI KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
The study aims to determine: (a) The influence of professionalism activity, principal leadership and participation in training on teacher performance. (b) The influence of professionalism activity on teacher performance. (c) The Influence of principal leadership on teacher performance. (d) The influence of participation in education and training on teacher performance.The study was conducted in Kebumen in the school year 2013/2014. The study uses a quantitative approach with a survey method. The technique of collecting data through questionnaires to study the form of a questionnaire instrument. Sample was 121 teachers on Junior High School teachers in ninth Sub-Rayon, Gombong, Kebumen Residence. Sampling technique in this study is proportional random sampling technique.The results showed that: (a) if teachers often carry out activities of professionalism, leadership learning principals and teachers performed well often follow the training activities can provide a very significant influence on the performance of teachers with effective contribution of 34.7%. (b) the teachers professionalism activities give effective contribution of 9.47% and the relative contribution of 27.32% on teacher performance. (c) the principal's leadership influence with the lowest effective contribution of 7.07% and the relative contribution of 20.40% on teacher performance. (d) participation in education and training provide the most impact on the performance of teachers with the effective contribution of 18.12% and 52.28% relative contribution.